The Relationship Between Knowledge and Husbands' Attitudes Regarding the Use of Condoms as a Contraceptive in Huraba Village - Triani, Meli (Cattleya Darmaya Fortuna, 2024)
A condom is a contraceptive device made of rubber/latex, shaped like an impermeable tube with a tightly closed end and equipped with a sperm collection pouch. To date, the increase in condom use has not met the target, reaching only 41%. The purpose of this study was to determine the relationship between knowledge and husbands' attitudes regarding condom use as a contraceptive in Huraba Village, Siabu District, Mandailing Natal Regency in 2024. This research is a correlation study using a cross-sectional design. The data sources are primary and secondary data, using a questionnaire as an instrument, and analysis using the chi-square statistical test using SPSS (Statistical Product and Service Solution). The sample size for this study was 38 husbands. Based on the research results table on the relationship between knowledge and husband's attitudes regarding condom use as a contraceptive, the results obtained from the Chi-Square test table in the Asymp. Sig. (2-sided) column show the probability value. The sig. value is 0.000, which means that the value (p<0.05) and the calculated χ2 value = 30.968 > χ2 table = 5.991 with df = 2 and a significance level of 0.05%. From the results of the study of 38 respondents, it can be concluded that husbands' knowledge about the use of condoms as a contraceptive is